KORELASI KUAT TEKAN HAMMER TEST (NON DESTRUCTIVE TEST) DAN CORE DRILL (SEMIDESTRUCTIVE TEST) DI GEDUNG KANWIL BRI TEUKU UMAR PRA REKONSTRUKSI - Sitorus, Mentari Septanya; Zhafira, Talitha; Purwanti, Hani (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The Jatingaleh BRI Regional Office is one of the buildings in Central Java that will be reconstructed. This is done to improve the function of the building with new reinforcement. One of the processes before being reconstructed is to check the compressive strength of concrete by means of a non-destructive test using a hammer test & semi destructive using a core drill. One of the factors that affect the strength of concrete is surface hardness. The method used in this study was to collect primary data in the form of hammer test results, compressive strength test results using the core drill method and secondary data obtained from the contractor. The purpose of this study is expected to be able to determine the correlation of compressive strength with the hammer test method and the core method. After carrying out the hammer test, proceed with the core drill test. Based on the research results, the compressive strength correlation was obtained using the hammer test and core drill method which is presented by an equation ðŸ.ðŸ‘ðŸðŸ•ðŸ–ð’†ðŸŽ.ðŸŽðŸ“ðŸ”ðŸ•ð’™ with a value of ð‘¹ðŸ=ðŸŽ.ðŸ–ðŸðŸðŸ”.